Combination treatment with anti-HER2 therapeutic antibody RC48, PD-1 inhibitor, radiotherapy, and granulocyte macrophage-colony stimulating factor (GM-CSF) in patient with metastatic gastric cancer: a case report - Liu, Zhuixing; Wang, Fang; Zhang, Yingqi; Lu, Jun; Yang, Yang (Frontiers in Immunology, 2024)
HER2 overexpression/amplification is a prevalent driver in various types of cancer,including gastric cancer (GC).Limited options are available for patients with HER2-positive metastatic gastric cancer,particularly those who do not respond to the standard therapy of HER2 antibody trastuzumab combined with chemotherapy.Previous research suggests that combining a PD-1 inhibitor with radiotherapy and granulocyte macrophage-colony stimulating factor (PRaG regimen) may enhance the antitumor effects in patients with chemotherapy-resistant metastatic solid tumors.In this case study,we presented a potential treatment strategy of a patient having HER2-positive and PD-L1negative gastric adenocarcinoma.The patient showed rapid tumor progression even after surgery and multiple trastuzumab plus chemotherapy treatments.To address this,we employed a novel anti-HER2 antibody called RC48 in combination with PRaG regimen therapy (PRaG3.0).The patient demonstrated a positive response after two treatment cycles and achieved a progression-free survival time of 6.5 months.This case highlights the potential of four-combination therapies for treating refractory,multiorgan,HER2-positive,PD-L1-negative metastatic gastric cancer.Additionally,varying radiation doses in targeting dual foci is critical to enhance tumor immunotherapy.